2005
DOI: 10.1073/pnas.0504270102
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and estradiol-dependent changes in gonadotropin-releasing hormone neuron firing activity

Abstract: A robust gonadotropin-releasing hormone (GnRH) surge is a prerequisite signal for the luteinizing hormone (LH) surge that triggers ovulation. In rodents, the GnRH surge is initiated by elevated estradiol and a diurnal switch in estrogen action from negative to positive feedback. The ability of constant estradiol treatment to induce daily LH surges was tested in adult mice that were ovariectomized (OVX) or OVX and treated with estradiol implants (OVX؉E). LH in OVX mice showed no time-of-day difference. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
213
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(238 citation statements)
references
References 76 publications
20
213
3
2
Order By: Relevance
“…As expected, the uterine weights of the E2-treated group (152 Ϯ 10.5 mg) were significantly greater than the uterine weight of the oil-treated group (21 Ϯ 1.4 mg), indicative of the circulating levels of estrogen (Christian et al, 2005). However, neither Kir6.2 nor SUR1 mRNA expression was altered with estrogen treatment (Fig.…”
Section: Expression Of Kir62 and Sur1 Transcripts In Gnrh Neuronssupporting
confidence: 65%
See 1 more Smart Citation
“…As expected, the uterine weights of the E2-treated group (152 Ϯ 10.5 mg) were significantly greater than the uterine weight of the oil-treated group (21 Ϯ 1.4 mg), indicative of the circulating levels of estrogen (Christian et al, 2005). However, neither Kir6.2 nor SUR1 mRNA expression was altered with estrogen treatment (Fig.…”
Section: Expression Of Kir62 and Sur1 Transcripts In Gnrh Neuronssupporting
confidence: 65%
“…In addition, female mice used for the scPCR and real-time PCR were either intact or ovariectomized, implanted with oil or E2 capsules, and given a single injection of oil (100 l) or estradiol benzoate (EB) (2 g in 100 l of oil, which yields plasma E2 levels of ϳ75 pg/ml) 24 h before the experiment. The animals were killed at 10:00 A.M. during negative feedback (Christian et al, 2005). This supplemental estrogen treatment was used to increase mRNA expression, although it did not alter the E2-induced current.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that GnRH firing activity is modified by estradiol in a diurnal-dependent manner (47), and that COX-2 expression in the preoptic region is greater in males than females (48). Perhaps the lack of changes in GnRH firing activity is related to the fact that all recordings were made at the same time of day and using a saturating dose of PGE 2 .…”
Section: Discussionmentioning
confidence: 96%
“…The purpose of this experiment was to test the model that GPR54 signaling mediates the positive feedback effects of E on LH secretion. To accomplish this, we used a protocol that was previously shown to induce a daily, evening LH surge in mice (Christian et al, 2005). Adult female WT and GPR54 KO mice were subjected to the LH surge protocol as described below.…”
Section: Experimental Designmentioning
confidence: 99%
“…We used the protocol devised by Christian et al (2005) to induce a predictably timed LH surge in adult female mice. Briefly, on the morning of day 0, mice were anesthetized by inhaled isofluorane, and the ovaries were removed through bilateral incisions.…”
Section: Induction Of Daily Lh Surgementioning
confidence: 99%